Antioxidant and antiproliferative activity of ethanolic and aqueous extracts from leaves and fruits juice Passiflora edulis - Johanny Aguillón Osma; María Elena Maldonado; Nelsy Loango Chamorro; Sandra Sulay Arango Varela; Patricia Landázuri (Universidad de Antioquía, 2013)
Background: Extracts from a variety of fruit trees have been used for therapeutic applications for preventing oxidative stress associated to chronic diseases. Objective: To investigate the antioxidant and antiproliferative activity of ethanolic and aqueous extracts from leaves and fruits of Passiflora edulis. Materials and methods: A preliminary phytochemical screening was performed; antioxidant activity was evaluated through DPPH assay, the scavenging activity for hydroxyl radical, antihemolytic activity and total phenolic content; cytotoxic and antiproliferative activities were evaluated by MTT and sulforhodamine B assays respectively in colon adenocarcinoma SW480 cells and their metastatic-derived SW620 cells. Results: Phytochemical analyses revealed presence of tannins, flavonoids and cardiotonic glycosides. Ethanolic extract from leaves showed the best antioxidant activity (EC50 = 0.096 mg/ml) in the DPPH assay and the juice (EC50 = 0.022 mg/ml) for the Hydroxyl free radical-scavenging activity. All extracts inhibited more than 98% the hemolysis induced by H2O2. The aqueous extract from leaves showed the highest cytotoxic activity against SW480 and SW620 cells. Conclusions: Findings from this study suggest that P. edulis is a potential source of phytochemical compounds with antioxidant and antiproliferative properties.